Genome-wide analysis of the GRAS gene family in white clover (Trifolium repens L.) provides insight into its critical role in response to cold stress - Mingxiang Huang; Guifeng Zhang; Haoyun Gan; Chuang Liu; Manman Li; Yongjun Shu (Biotechnology & Biotechnological Equipment)
The GRAS transcription factor (TF) is a plant-specific regulator that plays a critical role in plant growth, development and response to various abiotic stresses. While the functions of many GRAS TFs have been extensively studied in numerous model plants with fully sequenced genomes, the GRAS TFs in white clover (Trifolium repens L.) remain elusive despite the sequencing of its genome. To bridge this knowledge gap, homologs of GRAS TFs from Arabidopsis were employed and subjected to a genome-wide blast against white clover proteins. This analysis identified and characterized 102 putative GRAS genes, designated as TrGRAS, based on the presence of GRAS domains in positive blast hits. Concurrently, an exploration of their gene structures, classification, evolutionary relationships and conservative motifs provided insights into the distinctive features of TrGRAS in white clover. Furthermore, gene duplication analysis revealed an expansion of TrGRAS genes in the PAT1 and LISCL subfamilies, indicating functional diversity within the white clover genome. Lastly, RNA-seq and quantitative reverse transcription-PCR (qRT-PCR) experiments confirmed their higher expression during the early or intermittent responses to cold stress, suggesting their potential and crucial roles in determining the cold tolerances of white clover. The analysis of TrGRAS genes, coupled with expression studies, contributes to the functional characterization of TrGRAS genes in white clover. This knowledge is pivotal for informing genetic improvement strategies in future breeding efforts aimed at enhancing cold tolerance in white clover.